Effect of Discharge and Pressure on the Performance of Crossflow Turbine Simulation System - Rahmat Afdhol; Arwizet Karudin; Remon Lapisa; Andre Kurniawan; Soretire Lanrewaju Kamorudeen (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
The demand for electrical energy is increasing. Electricity supply in Indonesia is not yet evenly distributed. Indonesia's electrification ratio is only 99.63%. Generally, areas that have not been electrified are rural areas. It is necessary to utilize water energy sources for power generation. This research was conducted with a simulation tool from a micro hydro power plant with a crossflow turbine. The use of this turbine is because it is easy in terms of cost and manufacturing. The research was given an input source from a pump with a double pump system and a single pump system. Each system is given a variation of 100%, 75% and 50% openings. Data collection time is carried out for 90 minutes on each system and opening. From the research results obtained current, voltage, and output power. In the double pump system with 100% opening is relatively greater than 75% and 50% opening in the same system and in the single pump system. The maximum output current obtained in this study is 0.09 amperes with a double pump system opening 100% and the minimum output value is 0.02 amperes in a single pump system opening 50%. The maximum output power obtained in this study was 1.81 watts with a 100% opening dual pump system and a minimum output value of 0.32 watts in a 50% opening single pump system. The maximum output voltage obtained was 21.5 volts at 50% opening of the dual pump system, and the minimum output voltage was 15.8 volts at 50% opening of the single pump system. A large discharge will provide a large current, voltage and power output because it is able to crush the turbine with a relatively large speed. Discharge will affect the pressure and flow that occurs in the pipe, because the amount of discharge will be linear with the amount of pressure. The use of double pumps will get high efficiency with a large discharge. The greatest efficiency occurs when the double pump system.